BRICS: An Opportunity for a Transformative South?. (March 2014) - Sarkar, Urvashi
Brazil, Russia, India, China and South Africa (BRICS) have received considerable analysis as a group attempting to present an alternative to West-driven institutions and hegemony. While its formation is a positive development for the South, it requires to reach out to civil society. BRICS, minus a robust civil society involvement, will only result in entrenching viewpoints that see the BRICS as representing narrow business interests of a southern elite, with little concern for the gamut of socio-economic problems confronting the people of Southern nations.